Information Technology in Bio- and Medical Informatics : 6th International Conference, ITBAM 2015, Valencia, Spain, September 3-4, 2015, Proceedings - Renda, M. Elena; Bursa, Miroslav; Holzinger, Andreas; Khuri, Sami.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 6th International Conference on Information Technology in Bio- and Medical Informatics, ITBAM 2015, held in Valencia, Spain, in September 2015, in conjunction with DEXA 2015. The 9 revised long papers presented together with 1 poster paper were carefully reviewed and selected from 15 submissions. The papers address the following two topics: medical terminology and clinical processes and machine learning in biomedicine.
Keywords: Data mining; Medical records -- Data processing; Database management; Computer science; Bioinformatics; Data Mining and Knowledge Discovery; Health Informatics; Information Systems Applications (incl. Internet).; Database Management; Mathematical Logic and Formal Languages; Computational Biology/Bioinformatics.